Accountability and secrecy in the Australian intelligence community: the Parliamentary Joint Committee on intelligence and security - Bolto, Richard (2019)
The Parliamentary Joint Committee on Intelligence and Security is a significant, evolving and little-known accountability mechanism. As the basis of a case study, publicly available committee documents offer valuable insights into accountability practices within an unusual area of government. These documents highlight a range of accountability exchanges and broader relationships, as well as some of their defining features. Exploring critical institutional factors requires conceptual clarity about accountability and what makes it effective or ineffective. An accountability forum can thus be examined as a social mechanism through which the key stages of accountability unfold, at least in theory. Secrecy is a potentially significant intervening variable in this case, but by applying democratic and constitutional perspectives on accountability, some more general strengths and weaknesses are evident. - Reproduced.
Keywords: Public information - Australia; Transparency